Community Participation in Reducing Flood Disaster Risk in Batu Merah Village, Sirimau District, Ambon City - Osok, Rafael Marthinus; Riry, Roberth Berthy; LaUo, Novanti (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
Natural disasters, including floods, are likely to occur in Maluku Province. Flood is the inundation of rivers caused by heavy rain or flooding caused by transmission from higher elevations. This study aimed to determine the extent and form of community involvement in reducing the risk of flooding in the Batu Merah Village, Sirimau District, Ambon City. This study uses descriptive qualitative research, or descriptive techniques, primarily focused on identifying problems using data collected from the field. But can also offer interpretation or analysis. The results showed that the participation of the Batu Merah community in reducing the risk of flood disasters in Batu Merah Village, Sirimau District, Ambon City was the most or the largest, namely Very Often with an average number of respondents of 20 (50.00%). Often with the number of respondents 10 (25.00), Rarely with the number of respondents 8 (20.00), and Never with the number of respondents 2 (5.00%) out of 40 respondents, and the form of participation in flood management is calm and money (100%).